New Data on the Environment of N. S. Leskov in the Orel Province - Elena N. Ashikhmina (Два века русской классики, 2022)
The article reveals unknown pages of the biography of the writer N. S. Leskov’s father — S. D. Leskov, as well as the Strakhov family, close acquaintances of the Leskovs. The article contains biographies of the prototypes of N. S. Leskov’s characters, his estate neighbors in the Kromsky district. For the first time, data are presented on the previously unknown possessions of the Leskov family in the Kromsky district of the Oryol province. After the departure of the Leskovs from the province, they still owned small plots of land that connected the family with their native lands. The author of the article analyzes numerous documents from the State Archives of the Orel Region, the General Land Survey of the Kromsky District of the Oryol Province, on the basis of which observations are made of relatives, acquaintances, estate neighbors of the Leskov family. The paper shows how life facts of different importance and scale were used and generalized by the writer, getting into his creative laboratory.